Discrimination Between Individual Body Odors Is Unaffected by Perfume. (November 2019) - Gaby, Jessica M.; Dalton, Pamela
Body odor conveys personal information and is important in social evaluations and bonding. As most body odor research uses samples devoid of exogenous fragrances, we asked whether fragrances interact with body odor to change social olfactory information. We investigated whether (a) aversive conditioning could induce learned responses to individual body odors, (b) the addition of perfume worn by the odor donor alters this effect, and (c) this conditioned response affects the interpretation of visual information. Participants underwent classical (electric shock) conditioning with perfumed or unperfumed body odors as stimuli. During acquisition phase, we monitored galvanic skin response. After conditioning, participants rated the emotions of neutral faces in the presence of both conditioned and control odors. Increased galvanic skin response activity when smelling the conditioned odor on unshocked trials ( p = .041) suggested successful conditioning. We found no differences in conditioning success between perfumed and unperfumed body odors, suggesting that perfume does not mask individual differences. Participants perceived neutral faces as more surprised when smelling the conditioned odor ( p = .001), suggesting that olfactory stimuli may modify social perception in other modalities. Sharing emotional experiences with another individual, necessarily in the presence of their body odor, may affect future interactions with and assessments of that person.